Bacteriome genetic structures of urban deposits are indicative of their origin and impacted by chemical pollutants. Issue 1 (December 2017) - Marti, Romain; Bécouze-Lareure, Céline; Ribun, Sébastien; Marjolet, Laurence; Bernardin Souibgui, Claire; Aubin, Jean-Baptiste; Lipeme Kouyi, Gislain; Wiest, Laure; Blaha, Didier; Cournoyer, Benoit
Abstract Urban activities generate surface deposits over impervious surfaces that can represent ecological and health hazards. Bacteriome genetic structures of deposits washed off during rainfall events, over an urban industrial watershed, were inferred from 16 S rRNA gene (rrs ) sequences generated by high throughput sequencing. Deposits were sampled over a 4 year-period from a detention basin (DB). Major shifts, matching key management practices, in the structure of these urban bacteriomes, were recorded. Correlation analyses ofrrs similarities between samples and their respective concentrations in chemical pollutants, markers of human fecal contaminations (HF183) and antimicrobial resistances (integrons), were performed. Harsher environmental constraints building up in the older deposits led to an increase number ofrrs reads from extremophiles such asAcidibacter andHaliangium . Deposits accumulating in the decantation pit of the DB showed an increase inrrs reads from warm blooded intestinal tract bacteria such asBacteroides andPrevotella . This enrichment matched higher concentrations ofBacteroides HF183 genotypes normally restricted to humans. Bacteriomes of urban deposits appeared good indicators of human-driven environmental changes. Their composition was found representative of their origin. Soil particles and rain appeared to be major contributors of the inferred bacterial taxa recovered from recent deposits.